Uncovering the Macrostructure of Tourists Preferences. A Choice Experiment Analysis of Tourism Demand to Sardinia - Rinaldo Brau; Davide Cao (Fondazione Eni Enrico Mattei (FEEM), 2006)
This paper studies the preferences of tourists visiting the island of Sardinia (Italy), by means of a choice modelling approach. The focus is on some specific demand-enhancing effects which should confirm the feasibility of implementing sustainable tourism policies. Multinomial logit estimations reveal the strong negative effects resulting from the congestion of tourist attractions and the major transformation of coastal environments. On the other hand, recreational services and the proximity of accommodation to the beaches also seem to be important. The computation of willingness to pay measures and choice probabilities for hypothetical destinations illustrate how this kind of approach can provide useful information in determining decision processes by policy makers and development agencies.
Keywords: Q56; L83; C25; 330; Tourism demand; Green preferences; Choice experiments; Stated preferences; Tourismus; Nachfrage; Offenbarte Präferenzen; Sardinien